1990
DOI: 10.1111/j.1095-8649.1990.tb05028.x
|View full text |Cite
|
Sign up to set email alerts
|

Sturgeons (Pisces: Acipenseridae); threats and prospects

Abstract: Life histories of 24 species of sturgeons are briefly summarized and threats to their existence are reviewed. The most important of these are fishing and physical disturbance of rivers (barriers; fluctuating water levels; gravel extraction). Conservation measures to limit and compensate for these impacts are reviewed. In Europe the common sturgeon, Acipenser srurio, is an endangered species; it has been the object of a conservation programme in France since 1982.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(128 citation statements)
references
References 0 publications
4
123
0
1
Order By: Relevance
“…Adequate national and international funding must be provided to enable further research on the biology of sturgeons and paddlefishes and to support immediate measures for their protection. Moreover, management efforts and funding should be directed at the most threatening impacts, such as habitat fragmentation and habitat loss, as well as bycatch or poaching (Rochard et al 1990). Recent research has provided agencies with effective tools to identify and prioritise conservation measures with which to in crease the effectiveness of investment in species protection and risk mediation , Linke et al 2011.…”
Section: Recommendations For Future Research and Managementmentioning
confidence: 99%
“…Adequate national and international funding must be provided to enable further research on the biology of sturgeons and paddlefishes and to support immediate measures for their protection. Moreover, management efforts and funding should be directed at the most threatening impacts, such as habitat fragmentation and habitat loss, as well as bycatch or poaching (Rochard et al 1990). Recent research has provided agencies with effective tools to identify and prioritise conservation measures with which to in crease the effectiveness of investment in species protection and risk mediation , Linke et al 2011.…”
Section: Recommendations For Future Research and Managementmentioning
confidence: 99%
“…However, knowledge about young stages of this species in the wild is limited (Acolas et al 2011b). The specific needs of this migratory species with regard to habitat, as well as vulnerability during migration, due to overfishing and habitat degradation are major factors involved in population collapse over the past few decades (Rochard et al 1990). One species restoration action consists of developing a captive stock to produce offspring for release in river systems in an attempt to boost natural populations (Chebanov et al 2011;IUCN/SSC 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, when in the sea, the Italian sturgeon seems to remain near the estuaries (Paccagnella, 1948). Rochard et al (1990) identified three types of life history for the sturgeons and assigned the Italian species to type 2. After spawning, the adults migrate to brackish waters, later followed by the juveniles.…”
Section: Introductionmentioning
confidence: 99%